PENGGUNAAN KORTIKOSTEROID PADA SINDROM HELLP - Fakhri Wisa Amrulloh; Ratna Dewi Puspita Sari (STIKES Syedza Saintika Padang, 2022)
Background: Hypertension in pregnancy is one of the main causes of maternal morbidity and mortality. HELLP syndrome is potentially life-threatening to the mother. Currently the main treatment for HELLP syndrome is symptomatic. Corticosteroids can be used to treat the patient's condition and promote fetal lung maturation. Methods: The research method used is a literature review, namely literature collected from various sources related to the use of corticosteroids in the HELLP syndrome. Results: The typical clinical symptoms of HELLP syndrome were right upper quadrant abdominal pain, nausea, and vomiting. At less than 27 weeks of gestation, conservative therapy is considered. Corticosteroids are important therapeutic agents used to treat allergic and inflammatory disorders or to suppress unwanted immune systems. Steroid molecules diffuse across cell membranes and bind to glucocorticoid receptors, causing a conformational change in the receptor thereby inhibiting transcription factors that control the synthesis of proinflammatory mediators. Another important effect is the inhibition of phospholipase A2, which is responsible for the production of many inflammatory mediators. Several studies showed that there was no difference in outcome between the treatment group and the control group. Other references say the use of corticosteroids in preterm pregnancy has shown beneficial results. Conclusion: The use of corticosteroids in the HELLP syndrome of preterm pregnancy has been shown to be beneficial.Keyword: Corticosteroid, HELLP syndrome, Pregnancy